Egg investment in response to helper presence in cooperatively breeding Tibetan ground tits. (4th July 2019) - Zhao, Qingtian; Hammers, Martijn; Li, Chen; Zeng, Xixia; Hao, Chenxi; Lu, Xin; Komdeur, Jan
Abstract : Life‐history theory predicts a trade‐off between current and future reproduction to maximize lifetime fitness. In cooperatively breeding species, where offspring care is shared between breeders and helpers, helper presence may influence the female breeders' egg investment, and consequently, survival and future reproductive success. For example, female breeders may reduce egg investment in response to helper presence if this reduction is compensated by helpers during provisioning. Alternatively, female breeders may increase egg investment in response to helper presence if helpers allow the breeders to raise more or higher quality offspring successfully. In the facultatively cooperative‐breeding Tibetan ground tit Pseudopodoces humilis, previous studies found that helpers improve total nestling provisioning rates and fledgling recruitment, but have no apparent effects on the number and body mass of fledglings produced, while breeders with helpers show reduced provisioning rates and higher survival. Here, we investigated whether some of these effects may be explained by female breeders reducing their investment in eggs in response to helper presence. In addition, we investigated whether egg investment is associated with the female breeder's future fitness. Our results showed that helper presence had no effect on the female breeders' egg investment, and that egg investment was not associated with breeder survival and reproductive success. Our findings suggest that the responses of breeders to helping should be investigated throughout the breeding cycle, because the conclusions regarding the breeders' adjustment of reproductive investment in response to being helped may depend on which stage of the breeding cycle is considered.